Effects of training duration and the role of gender on farm participation in water user associations in Southern Tajikistan: Implications for irrigation management - Balasubramanya, Soumya (International Water Management Institute, 2018)
Presented by Soumya Balasubramanya (IWMI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.